DIGITAL PATH OF THE HYPERTENSIVE PATIENT BEFORE A FIRST VISIT IN A TERTIARY CARE HYPERTENSION UNIT: A REAL-LIFE PILOT STUDY. (April 2021) - Postel-Vinay, Nicolas; Gardini, Margherita; Nogueira, Lima; Lorthoir, Aurelien; Amar, Laurence
Abstract : Objective: There is growing evidence that the information and communication technologies (ICT) can improve health care access, patient education, compliance or outcomes, particularly in chronic diseases such as hypertension. In this e-Health context, our group validated, several years ago, a standardized patient self-questionnaire (Hy-Quest) and a software system to help patients manage Home Blood Pressure Measurement (Hy-Result software). But to what degree can patients use ICT before any face to face contact with a health care professional? Design and method: Between October 2017 and October 2018, 304 patients booked an appointment through the website of an ESH Excellence Centre, (www.centre-hypertension.org ). Among them, 81% were first-visiting patients and 75% declared owning a sphygmomanometer. A simple, short E-mail was sent to a sample of 63 of them asking them to complete two tasks before attending their first appointment: ie. complete the Hy-Quest questionnaire (Hy-Q)and self-measure their blood pressure (BP), communicating their readings using the Hy-Result software (Hy-R). Results: Patients who responded were 56 (19-86) years old, had a mean office BP of 143/90 mmHg, a mean home BP of 137/84 mmHg under 1.8 antihypertensive drug/person. The mean duration of hypertension was 9 years (0–46). Attending their first visit, 54% of patients were able to successfully get through the digital path (27% completing Hy-Q+Hy-R; 25.4% Hy-Q only; 1.6% Hy-R only). Different problems (unattended or delayed visit, neither Hy-Q nor Hy-R completed, refusal to participate, computer problems) led the remaining 46% of patients to an unsuccessful digital path [Fig.]. Figure. No caption available. Conclusions: This pilot study shows that approximately half of the patients can contribute to preparing their first visit by going through a digital path starting from the online reservation, to filling in Hy-Quest and communicating their self-measured BP readings using the Hy-Result software. This study confirms the interest for continuing with a larger study to confirm these percentages, to gain a better understanding of the reasons that prevent the patient from preparing online for his first visit and subsequently, optimize the steps of the hypertensive patient's digital path.